2019
DOI: 10.1111/nph.15960
|View full text |Cite
|
Sign up to set email alerts
|

An AP2/ERF transcription factor ERF139 coordinates xylem cell expansion and secondary cell wall deposition

Abstract: Differentiation of xylem elements involves cell expansion, secondary cell wall (SCW) deposition and programmed cell death. Transitions between these phases require strict spatiotemporal control.The function of Populus ERF139 (Potri.013G101100) in xylem differentiation was characterized in transgenic overexpression and dominant repressor lines of ERF139 in hybrid aspen (Populus tremula 9 tremuloides). Xylem properties, SCW chemistry and downstream targets were analyzed in both types of transgenic trees using mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 60 publications
1
38
1
Order By: Relevance
“…On the other hand, we found that several genes that are involved in the negative regulation of trichome development were downregulated in trichomes, such as MYB82 (TEA023420), whose homologous gene was overexpressed in Arabidopsis, leading to reduced trichome numbers [10]. In this study, we found that some MYB (13), NAC (7), and WRKY (4) DEGs were trichome specific (Figure 4), and most trichome-specific genes were associated with cell wall synthesis, such as TEA013629 (homologues to AtNST1 gene) [64,65] and TEA007243 (homologues to AtMYB86 gene) [66], indicating that these TFs might be mainly involved in trichome development and growth regulation through modulating the cell wall or fiber synthesis. These trichome-specific TFs appear to participate in trichome elongation rather than initiation, and their potential functions in cell expansion and cell wall synthesis deserve further investigation.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, we found that several genes that are involved in the negative regulation of trichome development were downregulated in trichomes, such as MYB82 (TEA023420), whose homologous gene was overexpressed in Arabidopsis, leading to reduced trichome numbers [10]. In this study, we found that some MYB (13), NAC (7), and WRKY (4) DEGs were trichome specific (Figure 4), and most trichome-specific genes were associated with cell wall synthesis, such as TEA013629 (homologues to AtNST1 gene) [64,65] and TEA007243 (homologues to AtMYB86 gene) [66], indicating that these TFs might be mainly involved in trichome development and growth regulation through modulating the cell wall or fiber synthesis. These trichome-specific TFs appear to participate in trichome elongation rather than initiation, and their potential functions in cell expansion and cell wall synthesis deserve further investigation.…”
Section: Discussionmentioning
confidence: 63%
“…Accumulating evidence has demonstrated that ERF transcription factors may play roles in lignin biosynthesis and cell wall modification (Lee et al , ; Sakamoto et al , ; Taylor‐Teeples et al , ; Wang et al , ; Wessels et al , ). By phylogenetic analysis of the ERF superfamily, ClERF4 was found to be a member of the group IIId ERFs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…S3) are possibly involved in modulation of cellulose biosynthesis by transcriptionally regulating PCW‐type CESA genes (Saelim et al , ). Populus ERF139 , another group III ERF, was found to suppress vessel element expansion and stimulate guaiacyl‐type lignin accumulation (Vahala et al , ; Wessels et al , ). PpeERF2 was found to bind the promoter region to a cell wall degradation gene ( PpePG1 ) and thus to regulate peach fruit ripening (Wang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…1531–1543). A poplar gene encoding a poplar AP2/ERF class transcription factor, ERF139, was shown to affect multiple aspects of wood formation, including the radial expansion and dimensions of water‐conducting vessel elements, as well as positively influencing the deposition of the secondary cell wall chemical constituents of lignin and xylan (Wessels et al ., ).…”
Section: Structure and Function Of Woodmentioning
confidence: 97%